2012
DOI: 10.1007/s10620-012-2180-x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neutrophil Gelatinase-Associated Lipocalin Predicts Mortality and Identifies Acute Kidney Injury in Cirrhosis

Abstract: Background Kidney failure predicts mortality in patients with cirrhosis. Identification of kidney failure etiology and recognition of those at the highest mortality risk remains a challenge. Aims We hypothesized that urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) predicts mortality and identifies hepatorenal syndrome (HRS) in patients with cirrhosis. Methods Prospectively enrolled patients with cirrhosis were investigated by uNGAL immunoblot upon hospital admission. Kidney failure type was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(166 citation statements)
references
References 41 publications
10
152
0
4
Order By: Relevance
“…Among the most promising are neutrophil gelatinase-associated lipocalin (NGAL), IL-18, kidney injury molecule-1 (KIM-1), and liver-type fatty acid-binding protein (L-FABP). Although NGAL has been studied for early detection of AKI after liver transplantation (18,19) and for differential diagnosis of AKI in cirrhosis (20,21), few studies have evaluated these biomarkers for prognosis in patients with cirrhosis and AKI (20,21). With a unique mix of functional (HRS) and structural disease (ATN and GN), the association in cirrhosis between tubular injury biomarker levels and outcomes is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most promising are neutrophil gelatinase-associated lipocalin (NGAL), IL-18, kidney injury molecule-1 (KIM-1), and liver-type fatty acid-binding protein (L-FABP). Although NGAL has been studied for early detection of AKI after liver transplantation (18,19) and for differential diagnosis of AKI in cirrhosis (20,21), few studies have evaluated these biomarkers for prognosis in patients with cirrhosis and AKI (20,21). With a unique mix of functional (HRS) and structural disease (ATN and GN), the association in cirrhosis between tubular injury biomarker levels and outcomes is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies suggest that NGAL measurements either in urine and serum may differentiate acute tubular necrosis from type 1 HRS, pre-renal azotemia or chronic kidney disease [11]. Two recent studies suggest that elevated urinary NGAL is predictive of early mortality in cirrhotic patients with AKI [12,13]. However, NGAL lacks specificity as it is also elevated in other acute and chronic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in several clinical situations [39][40][41] have underlined that the NGAL increased two hours after the induction of AKI, before of the sCr elevation. In cirrhotic patients, preliminary studies have reported that NGAL levels were higher in those with HRS [42] compared to those without renal disease; NGAL was associated with the prediction of short-term mortality [43,44] and it could be used for differentiation of prerenal azotemia, acute tubular necrosis and HRS [45] . Urinary NGAL has been found to be 20 ng/mL in healthy population and in prerenal azotemia, 105 ng/mL in HRS, 325 ng/mL in AKI and 50 ng/mL in CKD [44] .…”
Section: Major Criteriamentioning
confidence: 99%